Preservation of old potato varieties - Schäfer-Menuhr, Angelika; Justus Liebig University Giessen (My University, 2001)
What are old potato varieties? A potato variety may be defined as a group of identical plants, sharing the distinctive characters of an original individual from whom they are derived by vegetative reproduction. A potato variety is considered distinct when it differs from all other known varieties by one or more recognizable characters whether they be of a morphological or of a physiological nature. Commercial potato cultivars are propagated through the tubers, since the propagation by seeds is hindered by a high degree of heterozygocity, selfincompatibility and male sterility, frequently accompanied by failures in fruit and seed set. In Germany for the commercialization of seeds of agricultural species and vegetables the addition to the National List is necessary. The German Seed Act (Rutz, 1999) provides the legal frame for the National List which protects the consumer and ensures the provision of high quality seed and planting stock material of resistant and high performance varieties forfarmers and horticulturists. When potato varieties are no longer on the official list they are considered as old potato varieties. Why does anyone want to preserve old potato varieties? As long as varieties are still on the market the breeders maintain the varieties. But what happens with those varieties not any longer on the National List? They find a refuge in collections of plant genetic resources also known as genebanks, otherwise they could be lostfor ever due to their requirements for vegetative propagation.
Keywords: ddc:630